Animated Transitions in Statistical Data Graphics - Heer, Jeffrey; Robertson, George (InfoVis 2007, 2007)
In this paper we investigate the effectiveness of animated transitions between common statistical data graphics such as bar charts, pie charts, and scatter plots. We extend theoretical models of data graphics to include such transitions, introducing a taxonomy of transition types. We then propose design principles for creating effective transitions and illustrate the application of these principles in DynaVis, a visualization system featuring animated data graphics. Two controlled experiments were conducted to assess the efficacy of various transitions types, finding that animated transitions can significantly improve graphical perception.